2013
DOI: 10.1002/hep.26184
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Liver-Specific Gene Polymorphisms and Their Expression Levels With Nonalcoholic Fatty Liver Disease

Abstract: Genetic factors account for a significant proportion of the phenotypic variance of nonalcoholic fatty liver disease (NAFLD); however, very few predisposing genes have been identified. We aimed to (1) identify novel genetic associations with NAFLD by performing a genome-wide association study (GWAS), and (2) examine the biological expression of the strongest genetic associations in a separate cohort. We performed GWAS of a populationbased cohort (Raine Study) of 928 adolescents assessed for NAFLD by ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…For control of NAFLD, the role of other players within the vitamin D pathway is worthy of further consideration. For example, circulating levels of the vitamin D binding protein GC inversely correlate with liver steatosis, and may determine the ability of vitamin D to modulate the development of NAFLD (37). In addition, 1,25(OH) 2 D may act through the vitamin D receptor to improve insulin sensitivity (38).…”
Section: Discussionmentioning
confidence: 99%
“…For control of NAFLD, the role of other players within the vitamin D pathway is worthy of further consideration. For example, circulating levels of the vitamin D binding protein GC inversely correlate with liver steatosis, and may determine the ability of vitamin D to modulate the development of NAFLD (37). In addition, 1,25(OH) 2 D may act through the vitamin D receptor to improve insulin sensitivity (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not have a healthy comparison population, reports of average VDBP levels in healthy children range from 232 to 298 mg/ml in pediatric populations of European ancestry using the same assay (52,53). A mean of 197 mg/ml was reported in young healthy children, 65% Hispanic and 23.4% African American, using a different assay (immunonephelometry) (39), whereas mean levels of 330 to 437 mg/ml have been reported in healthy children using radial immunodiffusion (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…This data indicate the existence of an important genetic basis for this disorder in that population. In order to discover single nucleotide polymorphisms (SNPs) associated with NAFLD, several genome-wide association studies (GWAS) have been carried out in HIV-uninfected individuals of several ethnicities [6][7][8][9][10][11]. These studies have identified several SNPs independently associated with NAFLD located within or close to different loci including PNPLA3, COL13A1, EFAB4B, EHBP1L1, FDFT1, GCKR, LYPLAL1, NCAN, PPP1R3B, GC, LCP1, LPPR4, SLC38A8, PARVB, and SAMM50 genes.…”
Section: Introductionmentioning
confidence: 99%